Educational attainment, brain cortical structure, and sarcopenia: a Mendelian randomization study - Zhang, Yunqing; Wang, Ruideng; Chen, Zhengyang; Zhou, Fang; Su, Shilong (Frontiers in Public Health, 2024)
Background: Previous observational studies have suggested associations between high-level educational attainment (EA) and a lower risk of sarcopenia. However, the causality inferred from those studies was subjected to residual confounding and reverse causation. The protective effect of EA on sarcopenia may be mediated via changes in brain cortical structure. The aim of this study was to use a two-step Mendelian randomization (MR) analysis to illustrate the causal relationship between EA, brain cortical structure, and sarcopenia.Methods: Instrumental variables at the genome-wide significance level were obtained from publicly available datasets, and inverse variance weighted as the primary method was used for MR analysis. We perform several sensitivity analyses, including Cochran Q test, MR-Egger intercept test, leave-one-out analyses, and MR Pleiotropy Residual Sum and Outlier to evaluate the reliability of the results.Results: EA was causally associated with increased appendicular lean mass (β=0.25, 95% confidence interval (CI): 0.19 to 0.31, P=2.25×10 -15 ), hand grip strength (left: β=0.042, 95% CI: 0.013 to 0.071, P=4.77×10 -3 and right: β=0.050, 95% CI: 0.022 to 0.079, P=5.17×10 -4 ), and usual walking pace (β=0.20, 95% CI: 0.18 to 0.22, P=6.16×10 -83 ). In addition, EA was associated with increased brain cortical surface area (β=4082.36, 95% CI: 2513.35 to 5681.38, P=3.40×10 -7 ) and cortical thickness (TH) (β=0.014, 95% CI: 0.0045 to 0.023, P=3.45×10 -3 ). Regarding the causal effect of EA on usual walking pace, the mediatory effect of TH was 0.0069 and the proportion of mediation by TH was 3.43%.The study will have revealed the protective causal effect of EA on sarcopenia, which provides a reference for the prevention of sarcopenia at the public health level. We also will have found EA could affect the brain cortical structure, and the brain cortical structure could mediate the protective effect of EA against sarcopenia risk.